Evolution of supraglacial lakes on the Greenland Ice sheet - Wendleder, Anna; Gnatzy, Gregor; Schmitt, Andreas; Abdullahi, Sahra (2021)
Polar Regions pass through dramatic changes caused by ongoing climate warming. In many areas, rapid glaciers surface velocity has been observed provoked by supraglacial lakes if their water is able to drain to the ground. This study analyses the evolution of supraglacial lakes on the western margin of Greenland near Kangerlussuaq based on a Sentinel-1 data time series from May to December 2017. Additionally, the TanDEM-X Digital Elevation Model is used for the determination of the altitude of the supraglacial lakes. The automatic detection of supraglacial lakes in SAR images is limited due to the very similar backscatter profile of water surfaces and wet glacier areas. Hence, we manually determined the lake boundaries and were able to date the onset, the maximum water level, and the drainage or freeze, respectively. We concluded that the time span between the onset and the maximal water level was two weeks for most of the lakes. Though, lakes above 1200 m a.s.l. freeze rather than draining out.